Computer Engineering: student's book - Evans V. Virginia (Career Paths)
Career Paths: Computer Engineering is a new educational resource for computer engineering professionals who want to improve their English communication in a work environment. Incorporating career-specific vocabulary and contexts, each unit offers step-by-step instruction that immerses students in the four key language components: reading, listening, speaking, and writing. Career Paths: Computer Engineering addresses topics including working with numbers, computer accessories, computer hardware, writing software, and operating systems. The series is organized into three levels of difficulty and offers a minimum of 400 vocabulary terms and phrases. Every unit includes a test of reading comprehension, vocabulary, and listening skills, and leads students through written and oral production. Included Features: A variety of realistic reading passages ; Career-specific dialogues ; 45 reading and listening comprehension checks ; Over 400 vocabulary terms and phrases ; Guided speaking and writing exercises ; Complete glossary of terms and phrases. The Teacher's Guide contains detailed lesson plans, a full answer key and audio scripts. The audio CDs contain all recorded material.